Performance of intercrops with various clones of eucalyptus planted under agrisilviculture system - Newaj, Ram; Handa, A.K.; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
A field experiment was conducted during 2003-2008 at National Research Centre for Agroforestry, Jhansi, Uttar Pradesh with four clones (C3, C6, C7 and C10) of Eucalyptus tereticornis (Smith) and two spacing (5 m × 4 m and 10 m × 2 m). Blackgram [Vigna mungo (L.) Hepper] – wheat [Triticum aestivum (L.) emend. Friori & Paol.] was grown as intercrop. The experiment was conducted in randomized block design with three replications. The growth of all the clones was better under pure plantation at beginning of the project but after that the growth of all clones was significantly higher in agrisilviculture than pure plantation. The variation in growth due to clone can also been seen but those clone perform better at beginning did not perform better regularly up to end of rotation. The grain yield of blackgram was higher (0.20 to 0.46 t ha-1) in 10 m × 2 m spacing over than 5 m × 4 m spacing (0.16 to 0.38 t ha-1) during different year but differences were not significant. The yield reduction in 5 m × 2 m spacing was higher (13.49 to 29.17%) as compared to 10 m × 2 m spacing (0.79 to 16.67%) over pure crop during different year. Similar results were also obtained in case of wheat but minimum reduction in grain yield under 5 m × 4 m spacing at beginning was 16.86% and it gone up to 51.85% after 7-year of plantation as compared to pure crop. The clonal variation in eucalyptus did not exhibit significant variation on yield of intercrops.